Sosialisasi Pencegahan Plagiarisme Pada Mahasiswa Untuk Meningkatkan Etika Akademik Di Era Digital - Nurul Ittaqullah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The development of digital technology and easy access to information have created new challenges in higher education, particularly regarding academic integrity and plagiarism among university students. Many students still lack understanding regarding plagiarism, citation ethics, paraphrasing techniques, and responsible use of digital resources and artificial intelligence in academic writing. This community service activity aims to provide socialization regarding plagiarism prevention to improve students’ understanding of academic ethics in the digital era. The activity was conducted through educational seminars, interactive discussions, demonstrations of plagiarism detection tools, and training on citation and paraphrasing techniques. The method used was descriptive qualitative with a participatory approach. Data collection techniques included observation, documentation, and participant responses during the activity. The results showed that the socialization activity positively impacted students’ understanding of plagiarism prevention, academic ethics, citation techniques, and responsible academic writing. Students also demonstrated increased awareness regarding the importance of originality and integrity in academic activities. Therefore, this activity is expected to become an initial effort in building academic integrity culture among university students in higher education environments